Methodological aspects of a comprehensive analysis of the fixed capital of machine building enterprises - Natalya V. Arsenieva; Lyudmila M. Putyatina; Natalia V. Tarasova (Economies, 2020)
The article examines in detail the main areas and methodological features of a comprehensive analysis of movement and use of fixed capital of machine building enterprises. The fixed capital of enterprises is particularly important in the process of economic activity and it requires considerable investment for development and improvement. The purpose of this study is to develop a comprehensive approach to the quantitative assessment of change in the fixed assets of enterprises, their structure, and efficiency of use.
Keywords: L23; E22; 330; fixed capital; fixed production capital; production capacity; efficiency of the fixed capital use; active and passive part of capital; capital productivity